The role of cognitive emotion regulation strategies in health related quality of life of breast cancer patients - Kovač, Aleksandra; Tovilović, Snežana; Bugarski Ignjatović, Vojislava; Popović-Petrović, Svetlana; Tatić, Milanka (Vojnosanitetski pregled, 2021)
Background/Aim. Breast cancer is often accompanied by patients’ unpleasant emotional states, which can significantly affect both the undergoing treatment and the quality of life of patients. The aim of this study was to examine the mediating role of cognitive emotion regulation strategies in relation between emotional distress and various aspects of patients’ quality of life, which would further indicate different psychotherapeutic interventions in psycho-oncological practice. Methods. The sample consisted of 97 breast cancer patients. Emotional distress was measured by the Depression Anxiety Stress Scale (DASS-21), cognitive emotion regulation strategies were measured using the Cognitive emotion Regulation Questionnaire (CERQ-36), while various aspects of health related quality of life were assessed using the Functional Assessment of Cancer Therapy-Breast (FACT-B) questionnaire. Multiple simultaneous mediations between variables were established using the process macro INDIRECT for SPSS. Results. Positive refocusing had positive effects both on physical [a = -0.83, b = 0.50, ab = -0.42, standard error (SE) = 0.14; 95% confidence interval (CI) = 0.17 – 0.83] and emotional well-being (a = -0.83, b = 0.29, ab = 0.24, SE = 0.13; 95% CI = -0.01 – 0.58) of the patients. Rumination negatively affected emotional well-being (a = -0.75, b = -0.33, ab = -0.25, SE = 0.16; 95% CI = -0.71 – -0.01) of the patients. Catastrophizing had a negative impact on social (a = 0.96, b = 0.12, ab = -0.12, SE = 0.13; 95% CI = -0.33 – -0.13) and functional well-being of the patients (a = 0.96, b = -0.16, ab = -0.15, SE = 0.09; 95% CI = -0.32 – -0.01). Conclusion. Positive refocusing, rumination and catastrophizing are significant cognitive coping strategies through which the intensity of emotional distress significantly changes, and this can be subsequently reflected in different aspects of patients’ health related quality of life. The above mentioned implies potential benefits of implementation of cognitive-behavioral trainings and interventions directed towards acquiring adaptive cognitive emotion regulation strategies, in order to improve the quality of life of breast cancer patients.
Keywords: breast neoplasms; quality of life; cognitive remediation; treatment outcome